Building Public Trust for Islamic Education - Eti Rohmawati (Tarbiyah Departement collaboration with AMCA, 2018)
Education is a conscious and planned effort to relize learning process, so the students actively develop their potentional to have religius spiritual strength, self control, personality, intelegence, noble character and the skill needed by themselves and the seociety. Trust in islamic education will not appear by itself. Trust will be arise when the institution shows its identity, process, program, plans, adventages and curricula that convince the islamic educational institution. Some strategy can be developed by marketing of islamic education, doing school review, quality control, banchmarking and enhancing participation leadership.